Bioinspired marine antifouling coatings: Status, prospects, and future. (February 2022) - Jin, Huichao; Tian, Limei; Bing, Wei; Zhao, Jie; Ren, Luquan
Abstract: Marine biofouling has negatively affected human sailing since ancient times. Traditional antifouling coatings were banned worldwide in 2003 due to their toxicity towards nontarget marine organisms. Consequently, the development of sustainable nontoxic antifouling coatings is urgent. Novel and exciting discoveries from nature have inspired us to design high-efficiency, environmentally compatible, and cost-effective antifouling coatings. This review focuses on six major bioinspired antifouling strategies: micro/nanostructured surfaces, natural antifoulants, bioinspired hydrogels, slippery liquid-infused porous surfaces, bioinspired dynamic surfaces, and zwitterionic coatings. This review provides insight into antifouling mechanisms, fabrication methods, and critical issues in the development of the six bioinspired antifouling strategies. This review also discusses current problems and future trends of bioinspired antifouling coatings. In practical applications, no single bioinspired antifouling approach can be identified as a universal antifouling strategy. This review introduces the multifunctional bioinspired antifouling strategy—a recent development that may address the existing problems in the single bioinspired strategy. The multifunctional strategy combines the synergistic strengths of multiple antifouling strategies, potentially enhancing the antifouling capabilities and lifespan of the coatings. This review may open a new horizon for the future development of bioinspired marine antifouling coatings.